Not Always a “Buffer”: Self-Compassion as Moderator of the Link Between Masculinity Ideologies and Help-Seeking Intentions After Experiences of Intimate Partner Violence - Komlenac, Nikola (Journal of interpersonal violence, 2023)
Many women and men experience intimate partner violence (IPV) during their lifetime. However, only relatively few people actually seek formal help after such an experience. The current study applied the mediated-moderation model of self-compassion and stigma that has previously been used to explain men’s help-seeking behavior for depressive symptoms. The current study analyzed whether conformity to masculinity ideologies (CMI), self-stigma, and self-compassion were related to women’s and men’s intention to seek formal help after IPV experiences. A cross-sectional online questionnaire study was conducted with 491 German-speaking participants (65.8% women/34.2% men; age: M = 36.1 years; SD = 14.2). Participants read three vignettes about experienced IPV and then indicated how likely they would be to seek medical or psychological help if they were in the main character’s situation. Additionally, the Conformity to Masculine Norms Inventory, Self-Stigma of Seeking Help Scale, and Self-Compassion Scale were used. Separate manifest path models for women and men revealed that strong CMI was linked to strong self-stigma in women and men. In turn, strong self-stigma was linked to weak intentions to seek formal help after IPV experiences. In men, strong self-compassion weakened (i.e., “buffered”) the link between CMI and self-stigma. However, direct associations between strong CMI and weak intentions to seek formal help remained, especially for those participants with strong self-compassion. The current study adds to the existing literature on associations between CMI, self-compassion, and self-stigma by showing that those links are also relevant in women. However, self-compassion might not always act as a “buffer” and mediators that explain links between strong CMI and weak intentions to seek formal help in people with strong self-compassion need to be found in future studies.